2020
DOI: 10.2147/opto.s198637
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Review of Contact Lens Dropout</p>

Abstract: Purpose: Contact lens (CL) dropout is likely a major factor contributing to the near stagnant growth in the CL market. The purpose of this review is to summarize the current state of knowledge related to the frequency of CL dropout and the factors associated with it. Methods: PubMed.gov was searched on or before March 22, 2020, with the terms "contact lens" with "dropout" or "cessation" or "disruption" or "discomfort". Pertinent articles were collected. The references from these articles were likewise searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 43 publications
5
67
1
Order By: Relevance
“…These dropout frequencies are on par with a recent review of contact lens dropout, which found a pooled contact lens dropout rate of 21.7% across studies that included both soft and/or rigid lens wearers (n = 8190). 16 The likely difference between the present investigation and the study of Ren et al is that the current study recruited uncomfortable soft contact lens wearers whereas Ren et al recruited myopic adults who had no contraindications for contact lens wear. Although any level of contact lens dropout is unwanted, the results presented here are promising in that they demonstrate that a large percentage of soft contact lens wearers can be fitted with a different lens modality and become successful wearers again.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These dropout frequencies are on par with a recent review of contact lens dropout, which found a pooled contact lens dropout rate of 21.7% across studies that included both soft and/or rigid lens wearers (n = 8190). 16 The likely difference between the present investigation and the study of Ren et al is that the current study recruited uncomfortable soft contact lens wearers whereas Ren et al recruited myopic adults who had no contraindications for contact lens wear. Although any level of contact lens dropout is unwanted, the results presented here are promising in that they demonstrate that a large percentage of soft contact lens wearers can be fitted with a different lens modality and become successful wearers again.…”
Section: Discussionmentioning
confidence: 68%
“…17 The current study and past work suggests that some lens wearers do have trouble learning how to apply and maintain gas permeable lenses, and therefore these patients should be closely monitored, especially early on in the fitting process, to ensure that they have everything they need to become successful lens wearers. 16,18 Another issue was that only 21% of subjects learned about orthokeratology from their primary eye care provider, which suggests that practitioners need to be better at educating their patients about all of their refractive error correction options. This need was highlighted by up to 82% of subjects, indicating that they wished that they had learned about orthokeratology sooner.…”
Section: Discussionmentioning
confidence: 99%
“…They contribute most of the tear film lipid layer which protects the aqueous phase from evaporating too quickly and also stabilises the tear film by lowering surface tension. Any abnormalities in Meibomian gland function and/or anatomy lead to reduced meibum secretion and/or altered lipid composition which in turn disrupt the ocular surface integrity and influence contact lens success [54][55][56].…”
Section: Meibomian Gland Changesmentioning
confidence: 99%
“…Previous literatures have stated that about 21%-64% of CL wearers discontinue CL use, while others are able to continue wearing their CLs well into their presbyopic years 2,3,4 . Contact Lens-related Discomfort (CLD) 5 is one of the major reasons for dropout rates in about 50% of CL users followed by dry eye (19.9%) 6 , ocular redness (6.8%) 6 , cost of CL (6.8%) 6 and handling issues (6.3%) 6 . Other factors include age, gender, presence of systemic disease, CL solution and care regimen, design, material, the modality of the contact lens 1,7 During a blink, the under surface of the eyelid interacts with the cornea and the conjunctiva 8 .…”
Section: Introductionmentioning
confidence: 99%